The Effect of Different Substrates on Laboratory Scale Cultivation of Kappaphycus alvarezii - Muhammad Heri Hariadi; Nunik Cokrowati; Mukammad Marzuki (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Seaweed is a leading commodity in the Indonesian fisheries sector. Indonesia is the second largest seaweed-producing country in the world after China. K.alvarezii is a type of seaweed that produces kappa carrageenan which can be used as a raw material in industry, making K.alvarezii seaweed very popular for cultivation. Cultivation of K.alvarezii seaweed has developed widely in Indonesian waters. The success of cultivating K.alvarezii seaweed can be achieved if it is supported by a suitable environment for its growth. One of the environmental aspects that influences the growth of K.alvarezii seaweed is the bottom substrate of the waters. This research aims to analyze the best substrate for the survival rate of brown K.alvarezii seaweed cultivated on a laboratory scale. This research used an experimental method using a Completely Randomized Design (CRD) consisting of 4 treatments and each treatment was carried out 3 times to obtain 12 experimental units. The treatments tested were different substrates consisting of sand, coral, volcanic rock, and coral sand. The results of the research show that different types of substrate have a real influence on the survival rate of brown K.alvarezii seaweed cultivated on a laboratory scale. Coral substrate gave the best results with a survival rate of 100%, final weight of 20 g, and carrageenan yield value of 26%.